Effect of copper on the growth of shrimps Litopenaeus vannamei： water parameters and copper budget in a recirculating system - 程波 刘鹰 杨红生 宋怿 李贤 (Chinese journal of oceanology and limnology, 2014)
Shrimps （Litopenaeus vannamei） were intensively cultured in a recirculating aquaculture system for 98 days to investigate effects of 0.3 mg/L Cu on its performance, Cu budget, and Cu distribution. Shrimps in Cu-treated systems had greater mean final weight （11.10 vs 10.50 g）, body length （107.23 vs 106.42 mm）, survival rate （67.80% vs 66.40%）, and yield （6.42 vs 5.99 kg/m3）, and lower feed conversion ratio （1.20 vs 1.29） than those in control systems but the differences were not significant. Vibrio numbers remained stable （10^4-10^6 colony forming units/mL） in the rearing tanks of both control and treated systems. Total ammonium-N, nitrite-N, nitrate-N, pH, chemical oxygen demand, 5-day carbonaceous biochemical oxygen demand, and total suspended solids were similar in controls and treatments. Dissolved Cu concentration in the treated systems decreased from 0.284 to 0.089 mg/L while in the control systems it increased from 0.006 2 to 0.018 mg/L. The main sources of Cu in the treated systems were the artificially added component （75.7% of total input）, shrimp feed （21.0%）, water （2.06%）, and shrimp biomass （1.22%）. The major outputs of Cu occurred via the mechanical filter （41.7%）, water renewal （15.6%）, and draining of the sediment trap （15.1%）. The foam fractionator removed only 0.69% of total Cu input. Harvested shrimp biomass accounted for 11.68% of Cu input. The Cu concentration of shrimps in the Cu-treated systems （30.70 mg/kg wet weight） was significantly higher than that in control systems （22.02 mg/kg）. Both were below the maximum permissible concentration （50 mg/kg） for Cu in seafood for human consumption in China. Therefore, recirculating systems can be used for commercial on-growing of Litopenaeus vannamei without loss of shrimp quality, even in water polluted by 0.30 mg/L Cu. The mechanical filter is the main route for Cu removal.